SISTEM INFORMASI AKUNTANSI MANAJEMEN KEUANGAN BERBASIS MULTI USER PADA KOPERASI AROFAH KENDAL - Sukemi Kamto Sudibyo; Dewi Astuty (LPPM Politeknik Pratama, 2023)
Currently, the majority of the Arofah Kendal Cooperative in financial management is still in the form of files, causing accumulation, damage, difficulty finding and even loss of financial data which has resulted in the Arofah Kendal Cooperative experiencing difficulties in presenting reports. The Arofah Kendal Cooperative always experiences an increase in transactions for the number of deposits and loans. The customer financial service system is centralized on one computer, so services must take turns, which takes a long time and is less effective. Implementing a Multi-User-Based Financial Management Accounting Information System, the Arofah Kendal Cooperative is able to overcome problems related to processing, financial filing and reporting. With a multi-user application, the database of the Arofah Kendal Cooperative is connected to each other to make it easier for each user to access the system according to authority simultaneously for data collection, financial transactions that can present up to date financial information according to the needs of cooperative management which provides effectiveness and efficiency in financial management, improves employee performance and maximizing customer service satisfaction for the Arofah Kendal Cooperative.